Review paper Microorganisms in the etiopathogenesis of atopic dermatitis - Pastuszka, Marta; Matych, Marta; Kaszuba, Aleksandra; Poznańska-Kurowska, Katarzyna; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Atopic dermatitis (AD) is a chronic, recurrent inflammatory skin disorder, which is accompanied by characteristic appearance of skin lesions and intense pruritus. The etiopathogenesis of the disease has not been fully elucidated. An important role in pathophysiology of AD seems to be associated with genetically related disturbances of both structure and function of the epidermal barrier, disorders in innate and adaptive immunity, the surrounding environment (airborne allergens and also food allergens – at the younger age) and infectious factors. The article presents current knowledge on the role of different microorganisms ( Staphylococcus aureus, Malassezia species, Candida species, Herpes simplex virus ) in initiating, exacerbation and maintaining skin lesions typical of atopic eczema.